106k views
1 vote
Complete the square x^2 - 6 + ____ = -13 + _____

User Erotavlas
by
5.4k points

2 Answers

5 votes

Answer:

x^2 - 6x + 9 = -13 + 9

Explanation:

x^2 - 6 + ____ = -13 + _____

I assume that the second term is -6x, not just -6.

x^2 - 6x + ____ = -13 + _____

To complete the square, take the x-term coefficient, -6, halve it, -3, and then square it, (-3)^2 = 9. Now add 9 to both sides.

x^2 - 6x + 9 = -13 + 9

User Dave Thompson
by
5.3k points
5 votes

Answer:

x^2 - 6x + __9__ = -13 + __9___

Explanation:

x^2 - 6x + ____ = -13 + _____

To complete the square

we take the coefficient of the x term, divide by 2 and square it

-6 /2 = -3

Then square it

(-3)^2=9

What we add to one side, we add to the other

x^2 - 6x + __9__ = -13 + __9___

User Danjp
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.